Gender roles and technological progress - Albanesi, Stefania; Olivetti, Claudia (Working paper series / National Bureau of Economic Research, 2007)
Until the early decades of the 20th century, women spent more than 60% of their prime-age years either pregnant or nursing. Since then, the introduction of infant formula reduced women's comparative advantage in infant care, by providing an effective breast milk substitute. In addition, improved medical knowledge and obstetric practices reduced the time cost associated with women's reproductive role. We explore the hypothesis that these developments enabled married women to increase their participation in the labor force, thus providing the incentive to invest in market skills, which in turn reduced their earnings differential with respect to men. We document these changes and develop a quantitative model that aims to capture their impact. Our results suggest that progress in medical technologies related to motherhood was essential to generate a significant rise in the participation of married women between 1920 and 1950, in particular those with young children.